2022
DOI: 10.1021/acs.orglett.2c01602
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of anti-[1](1,6)Naphthaleno[1](1,6)naphthalenophane by Double Contractive Annulation of [2.2]Paracyclophane

Abstract: Two-directional contractive annulation of [2.2]paracyclophane has led to the synthesis of anti- [1](1,6)naphthaleno [1](1,6)naphthalenophane (3). This [1.1]cyclophane (SE = 56.6 kcal/mol) consists of two bent and twisted naphthalene units with interplanar distances as short as 2.74 Å. Despite the high strain and structural distortion, 3 was found to be unreactive toward potential cycloaddition partners (TCNE, DMAD) and under UV irradiation.C ontractive annulation (CA) was recently developed as a new strategy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Increasing eccentricity was evident for compound 10 containing a 2,3‐dihydro‐1 H ‐phenalene moiety. In all cases, the seven‐membered rings adopt a boat conformation to minimize the strain of belts, with relatively large out‐of plane deformation of the naphthalene rings (see Supporting Information) [21] . The rigid belt structures also forced the −CH 2 CH 2 − group in 8 and 10 to adopt a nearly eclipsed conformation, increasing further the strain in the belts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing eccentricity was evident for compound 10 containing a 2,3‐dihydro‐1 H ‐phenalene moiety. In all cases, the seven‐membered rings adopt a boat conformation to minimize the strain of belts, with relatively large out‐of plane deformation of the naphthalene rings (see Supporting Information) [21] . The rigid belt structures also forced the −CH 2 CH 2 − group in 8 and 10 to adopt a nearly eclipsed conformation, increasing further the strain in the belts.…”
Section: Methodsmentioning
confidence: 99%
“…In all cases, the seven-membered rings adopt a boat conformation to minimize the strain of belts, with relatively large out-of plane deformation of the naphthalene rings (see Supporting Information). [21] The rigid belt structures also forced the À CH 2 CH 2 À group in 8 and 10 to adopt a nearly eclipsed conformation, increasing further the strain in the belts. It is worth stressing that the zigzagtype belt molecules obtained in the current study are greater in height than previously reported ones [4] thanks to the growth of fused rings on the edge.…”
Section: Methodsmentioning
confidence: 99%
“…1a, top). 8,9 Morisaki and co-workers reported the synthesis of [2.2][4]helicenophane by oxidative photocyclization of a planar chiral stilbene-type precursor. 8 As an exceptional example of the stereoselective direct linkage of two large PAHs with two-atom tethers, Bodwell and co-workers reported the isolation of planar chiral [2.2]pyrenophane as an unexpected side product from the intramolecular McMurry coupling of [10.2]pyrenophane-dialdehyde, presumably through the intramolecular McMurry coupling of the corresponding linear dialdehyde (Fig.…”
Section: Introductionmentioning
confidence: 99%